Clinical and pathological staging of primary carcinoma of the larynx - Hamza Al-badri, Musaid H.; Abbas Al- Rubai, Thamer M.; Salman, Ali L. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Staging of primary carcinoma of the larynx play an important role in surgical management of the disease .This staging depends on the clinical finding and radiological examination , supported by pathological assessment of the excised tumor Objectives: To evaluate the accuracy of clinical and radiological staging Patients’ and methods: Forty-two patients with laryngeal carcinoma were admitted to the ENT Department during the period from June 2009 through October 2010. Each patient was staged by clinical examination and computed tomography. Evaluation of the results compared to the final diagnosis of staging , based on the pathological staging of specimens of patients who underwent total laryngectomy and the highest T stage was obtained from clinical and CT staging for patients with early laryngeal carcinoma(T1-T2) . Results: The clinical staging of laryngeal carcinoma showed: high accuracy in staging was on glottic tumours (83.3%), especially T1 glottic tumours (100%),(small and superficial lesions), and lower accuracy in staging of supraglottic and transglottic tumors (61.9%) , (55.6% ) respectively.Underestimation of all tumors was 31.4% . The CT staging of laryngeal carcinoma showed: very high accuracy in staging transglottic and supraglottic tumours (100%), (85.7%) respectively in comparison to clinical staging and lower accuracy (75%) in staging glottic tumours. Underestimation of all tumours was 11.5 % of cases (especially small and superficial lesions). Conclusions: High accuracy rate based on clinical examination was found in glottic carcinoma and high accuracy rate based on radiological examination was found in supraglottic carcinoma. Clinical examination and CT scan are complementary for sraging of carcinoma of larynx .